(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The Schiff base ligand (E)-3-(2-methoxy benzylidene amino)-2-thioxothiazolidin-4-one (L), was prepared from N-amino rhodanine and 2-methoxy benzaldehyde . Moreover, Its complexes were synthesized by mixing metal chloride Co(II), Cu(II), Ni(II) with the prepared Schiff base ligand. These compounds were characterized by FTIR, 1H NMR, and elemental analysis. The antimicrobial activity of the ligand and its complexes were tested using four pathogenic bacterial and two fungal species. The bacterial species used in the screening were Salmonella typhi and Vibrio cholera (gram negative) and Staphylococcus aureus and Bacillus subtilis (gram-positive). The fungal species were Aspergillus flavus and Aspergillus nigar. The antimicrobial activities of the ligand and its metal complexes were studied by disc agar diffusion method and compared with Ampicillin. Diameter of inhibition zone (mm) including the disc diameter was measured for each treatment. The findings indicated that the CuL, NiL and CoL complexes have good biological activity but the ligand (L) did not had any activity against the microorganisms under identical experimental conditions.